Learning from your surroundings - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
In the struggle to raise literacy rates in ACP countries Education for all has long been a priority for ministries, international agencies and local NGOs. One approach is functional literacy, which has to be an integral part of the development...